Servicescape Analysis and Design for batagor Hanimun - Kurniawan, Ramara Arief; Hudrasyah, Herry (Journal of Business and Management, 2013)
Servicescape is one of the crucial elements in developing a restaurant. This also applies to Batagor Hanimun. Batagor Hanimun is a family business that starts in 2007 in Cimahi, and continues to grow until they already have 4 branches in Bandung as of now. The first servicescape elements problem that Batagor Hanimun had is that they haven’t got their own place. This makes them couldn’t alter the servicescape elements, and can only use what’s already provided for them from the place owner. The second problem is that there are no signages to indicate that Batagor Hanimun is there. This makes the brand virtually unknown to the new customers. The third problem is the servicescape elements didn’t justify the price given by Batagor Hanimun. Costumers complain that the price is too high without any added value from the service and place.The researcher did a direct observation to the place to start the research. Servicescape has a lot to do with sense: see, hear, touch, smell, taste. With this in mind, the researcher makes an observation based on the 5 senses, such as trying the different chairs and tables, touching walls and equipment material, etc. When designing the new servicescape design, the researcher makes the design with the assumption that the place used is in Ambon Street. This is due to the owner already has a plan to build their own place there. With that in mind, the researcher makes a new design specific for the target market there. The signage is put up front so that people can see it from the street. The design is based on some modern restaurant and café, while still maintaining the aspect of Bandung. The main focal point is the counter, with the wall made of stone and the name of the restaurant on the wall. The tables are made of wood, to maintain the traditional feel of Bandung. The seating is arranged into four categories: one person arrangement, two people arrangement, three to four people arrangement, and more than four people arrangement. This will make the place tidier, and the customers will have option as to what type of chairs they want to sit. Keywords: marketing, business strategy, servicescape, restaurant, branding-----------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.